Obstacle in implementing green building project in Malaysia / Farah Amira Hamzah - Hamzah, Farah Amira (Faculty of Architecture, planning and Surveying, 2015)
This research paper is about a study on an obstacle in implementing green building project in Malaysia. The objectives of this study are to study on principle in element of green building, to identify the obstacles in implementing green building projects in Malaysia and to provide the solution for the obstacles in implementing green building projects in Malaysia. The case studies are at KETTHA (LEO Building), Office of The Prime Minister of Malaysia (Jabatan Perdana Menteri) and Pejabat Menara Worldwide. The respondents are about 30 persons which is 10 persons for each case studies. The method used in this research are an interview, distribute some questionnaire and site visit survey. Moreover, to complete this research, secondary sources are used. Such as references of magazines, newspapers, articles and journals and also an official website (Internet).